Analisis Kebijakan Makan Bergizi Gratis Prabowo-Gibran dan Dampaknya Terhadap Kesehatan dan Bidang Pendidikan - Maliki, Alinda; Selvi, Nanda; Arifah, Amalia; Assa, Novel Stefly (Peneliti.net, 2025)
This study examines the policy of the Free Nutritious Food (MBG) program launched by the Prabowo-Gibran administration in October 2024, using a qualitative literature review methodology. The program targets 82.9 million beneficiaries across Indonesia with a budget allocation of IDR 71 trillion for the first year. The study examines three key dimensions: improvement of nutrition and health, educational performance and cognitive development, and socio-economic impact. The findings indicate significant potential to reduce the prevalence of malnutrition and enhance school participation and attendance. However, challenges arise regarding food safety management, fiscal sustainability, and quality control in 190 operational kitchens across various geographical contexts. This study reveals that a comprehensive life-cycle approach targeting pregnant women, breastfeeding mothers, toddlers, and school-aged children addresses the intergenerational malnutrition cycle more effectively than previous programs. The research findings indicate that school feeding program policies yield positive returns ranging from 4 to 16 for every dollar invested. The success of implementation depends on strengthening inter-ministerial coordination and robust monitoring mechanisms to ensure equitable distribution of resources across Indonesia.